Health Care Seeking Behaviors among General People in the Naogaon General Hospital of Bangladesh - Al Muksit Mohammad Taufiquer Rahman; Md Aminul Islam; Shanta Roy; Maisha Rahman Mohona (TAJ: Journal of Teachers Association, 2026)
Background: Health-seeking behavior is a critical determinant of health outcomes, particularly in low-resource settings like Bangladesh. Understanding why and how general people access hospital care can inform targeted interventions to reduce delays and improve service utilization. However, empirical data from secondary-level public hospitals remain limited. Objective: To assess the health care-seeking behaviors among the general population attending a district-level hospital in Bangladesh. Methods: A prospective cohort study was conducted at Naogaon General Hospital from January 2023 to April 2023. A total of 347 participants were selected using purposive sampling. Data were collected through face-to-face interviews using a semi-structured questionnaire. Analysis was performed using SPSS version 23.0, employing descriptive statistics to summarize demographic characteristics, illness types, time to consultation, and reasons for hospital choice. Results: Among 347 participants, 62.0% delayed care-seeking for ≥3 days, and only 27.7% completed treatment. Acute febrile illness (37.5%) was the commonest complaint. Affordability (57.6%) and proximity (45.0%) drove hospital choice, while long waiting time (52.4%) and drug unavailability (33.1%) were major barriers. Older age and low income were significantly associated with delayed care-seeking (p